ANALISIS KURIKULUM PONDOK PESANTREN MU'ADALAH SEBAGAI PEMBAHARUAN LEMBAGA PENDIDIKAN ISLAM - SURIP SURIP (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
By using a descriptive qualitative research method through a field study approach. Problem solving procedures are carried out based on problems that arise after being identified, regarding data collection techniques using observation, interviews, data collection and documentation techniques. The results of the research on this theme are that through the mu'dalam curriculum (hereinafter referred to as mu'dalam) Islamic educational institutions can develop the quality of education by creating alumni of Islamic boarding schools to continue their further education, either at home or abroad. The quality of Islamic educational institutions can be seen from the quality of their outcomes, the Al-Amanah Al-Gontory Islamic Boarding School has carried out an MOU with Al-Azhar Cairo in November 2021 as a form of improving the quality of future education, with the hope that alumni can continue the undergraduate program. 1st and 2nd strata in the pyramid country, while at the same time adding experience and insight in accordance with the five souls of the lodge, namely broad-minded. Through the mu'adah program with Al-Azhar Cairo for alumni of Islamic boarding schools as embryos for the development of knowledge and a form of renewal of Islamic educational institutions, besides that, students and teachers have the opportunity to take part in a cycle organized by Al-Azhar University for 3 (three) month, this can open up opportunities for improving the quality of Arabic knowledge and skills. With mu'adah, Islamic boarding schools no longer seem exclusive but are open at the level of inward looking (micro) and outward looking (macro). ABSTRAKDengan menggunakan penelitian Metode kualitatif deskriptif melalui pendekatan studi lapangan. Prosedur pemecahan masalah dilakukan berdasarkan permasalahan yang timbul setelah diidentifikasi, mengenai Teknik pengumpulan data menggunakan teknik observasi, wawancara, pengumpulan data dan dokumentasi. Hasil Penelitian dari tema ini bahwa melalui kurikulum mu'adalah (selanjutnya disebut mu'adalah) pada lembaga pendidikan Islam dapat mengembangkan mutu pendidikan dengan menciptakan alumni pondok pesantren untuk melanjutkan pendidikan tingkat lanjut, baik di dalam negeri atau di luar negeri. Kualitas lembaga pendidikan Islam bisa dilihat dari kualitas outcomenya, Pondok Pesantren Al-Amanah Al-gontory telah melakukan MOU mu'adalah dengan Al-Azhar cairo pada bulan November 2021 sebagai bentuk peningkatan mutu pendidikan masa depan, dengan penuh harapan agar alumni bisa melanjutkan program strata 1 dan strata 2 di negeri piramida, sekaligus menambah pengalaman dan wawasan sesuai dengan panca jiwa pondok yaitu berwawasan luas. Dengan melalui program mu'adalah dengan Al-Azhar cairo untuk para alumni pondok pesantren sebagai embrio pengembangan ilmu dan bentuk pembaharuan lembaga pendidikan Islam, salain itu santri dan guru mendapat kesempatan untuk ikut daurah yang diselenggarakan oleh pihak Universitas Al-Azhar selama 3 (tiga) bulan, ini bisa membuka peluang untuk peningatan kualitas ilmu dan keterampilan bahasa arab. Dengan mu'adalah maka pondok pesantren sudah tidak lagi terkesan eksklusif akan tetapi terbuka dalam tataran inward looking (mikro) dan outward looking (makro).